Dry matter accumulation during the grain-filling period in three maize hybrids - Ramos, Levi R. M.; Mundstock, Claúdio M. (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out at Guaíba, RS, Brazil, during the agricultural year of 1977/78 to determine the dry matter accumulation in the leaves, ear leaves, stalks, and ears of three maize (Zea mays L.) hybrids (Agroceres 28, Pioneer X 307 and SAVE 231). All of the hybrids showed the same behaviour, almost duplicating the dry matter quantity in that period. The dry matter was accumulated in the stalk and in the ear husk during the two first weeks and, later, mainly in the ear. Decreases in the dry matter of the aerial parts occurred between the grain-filling period and the physiological maturation as a consequence of the weight decrease in the stalks and leaves.